THE ROLE OF MIRRORING IN IMPROVING THE QUALITY OF INTERPERSONAL COMMUNICATION ON ENGLISH PODCAST “THERAPUSS WITH JAKE SHANE” - Yessika Apriani Simanihuruk; Anastasya Dwika Simanjuntak; Rita Hartati (ADISAM Publisher, 2025)
Mirroring is a behavioral phenomenon that helps foster connection and communication by prompting individuals to unconsciously mimic the words, body language, or facial expressions of their interlocutors. This study aims to examine the realization and application of NLP mirroring patterns in host and guest interactions on Therapuss with Jake Shane. Drawing upon the mirroring theory by Shlomo Vaknin (2008), this study utilizes a qualitative content analysis approach to identify and analyze the use of behavioral, symbolical, and exchanged match mirroring in conversations between Jake Shane (host) and Rose, Larray, and Tate (guests). According to the results, behavioral mirroring accounts for 61.22% of mirroring instances, symbolic mirroring for 30.61%, and exchanged matches for 8.16%. Behavioral mirroring is used most frequently, reflecting the repetition of words and gestures during interaction. These findings highlight the significance of mirroring in interpersonal communication, demonstrating its role in strengthening social bonds and shaping interpersonal exchanges. This study aims to contribute to a greater understanding of how NLP mirroring mechanisms are applied in digital media interactions.